ANALISIS BIAYA-VOLUME DAN LABA SEBAGAI ALAT PERENCANAAN LABA : (Studi Kasus Pada Unit Usaha Tahu Mas Ponimin Medan Polonia) - Sitanggang, Abdonsius (Jurnal Riset Akuntansi & Keuangan, 2023)
The purpose of this study is to analyze the Cost, Volume and Profit for January, February, March, April, May 2023 to plan profits specialy for June 2023. This type of research is descriptive with a quantitative approach. The data analysis method used in this study is Break Even Point, Contribution Margin, Margin of Safety, profit planning. Data collection techniques using interviews, observation, literature and documentation. The results of this study show that the calculation of the BEP (Rupiah) in January 2023 is IDR 21.583.224 while the BEP (Unit) is 863 tofu boards. Then for February the BEP is IDR 24.492.148 then the BEP (Unit) is 980 tofu boards. In March the BEP was IDR 25.655.050 and the BEP (Unit) was 1.026 tofu boards. For April, the BEP is IDR 22.199.727 and the BEP (Unit) is 888 tofu boards. And in May the BEP itself was IDR 20.362.298, and 814 units of tofu boards. In planning sales and profits, the Mas Ponimin Business Unit plans a profit for June of 5% of May profits. To achieve an increase in profit, it must increase sales by 13.363 units of tofu boards or Rp. 334.084.403. In conclusion, using Cost Volume Profit Analysis can find out how many units must be sold in order to obtain the desired profit from a plan.